THE FOREIGN ECONOMIC POLICY OF SMALL STATES IN THE CONTEXT OF GLOBALIZATION - Ashirova Gulchehra; Sotimova Anorjon Rashid qizi (Modern American Journals, 2025)
This article analyzes the impact of globalization processes on the foreign economic policy of small states. Due to the limited economic resources of small countries and the intense competition in international markets, their foreign economic activities have specific characteristics. The study examines the main directions of globalization such as trade, investment, technology flows, and labor migration, while also analyzing the experiences of Uzbekistan and other small states.
Keywords: Globalization, small state, foreign economic policy, international trade, investment, integration.